Hollywood quarterly : film culture in postwar America, 1945-1957 - Smoodin, Eric Loren; Martin, Ann, 1940- (University of California Press, 2002)
The first issue of Hollywood Quarterly, in October 1945, marked the appearance of the most significant, successful, and regularly published journal of its kind in the United States. For its entire life, the Quarterly held to the leftist utopianism of its founders, several of whom would later be blacklisted.
Keywords: Motion pictures -- United States.; Cinéma -- États-Unis.; PERFORMING ARTS -- Film & Video -- Reference.; PERFORMING ARTS -- Film & Video -- General.; Motion pictures; United States; Humaniora -- Film.; Motion pictures.; Films.